Effect of burial depth and soil water regime on the fate of Lithospermum arvense seeds in relation to burial time - Chantre Balacca, Guillermo Ruben (2009)
Lithospermum arvense is an increasing annual weed in winter crops of the semiarid region of southern Argentina under low impact tillage systems, an agricultural practice that has become popular in recent years. Seed distribution in the soil profile under conventional tillage will change when reduced tillage is implemented, thus affecting the germination microenvironment. The effect of seed burial depth and soil water regime on field germination, enforced dormancy, innate dormancy and seed decay was studied in relation to burial time in a field experiment. In addition, the effect of burial depth on seed germination and seedling emergence was examined under laboratory controlled conditions. Field germination of buried seed ranged from 55% to 65% for shallow (2 cm) and from 5% to 30% for greater depths (20 cm). Enforced dormancy levels were significantly higher among deeper seeds. The amount of innate dormant seeds was reduced to <10% after a year of burial. Lithospermum arvense seedbanks can be classified as short-term persistent. Germination in the laboratory was unaffected by burial depth, while seedling emergence reduction was adequately described by a sigmoidal model. Results indicate that agricultural practices that accumulate L. arvense seeds near the soil surface enhance seedling recruitment.